Increasing Physics Teacher Production by Replicating the UTeach Preparation Model and Awarding Noyce Scholarships - Hale, Gregory R.; Lopez, Ramon E.; Cavallo, Ann M. L.; Gonzales, Erin E. (Scientia in educatione, 2017)
In order to improve the production of physics teachers, and high school science teachers in general, at The University of Texas at Arlington, the authors obtained grant funding to offer National Science Foundation Robert Noyce Teacher Scholarships and to support a replication of the successful UTeach science and mathematics teacher preparation program. The Noyce grant was obtained first, and a modest increase in science teacher production was seen. The UTeach replication has been implemented on a four-year schedule, culminating in the establishment of a new student teaching program in January 2014. The combination of a UTeach replication and availability of Noyce Scholarships has UT Arlington poised to improve its science teacher production by an order of magnitude.